Antinomias e "suturas" epistemológicas entre biológico-social e individual-coletivo no âmbito da epidemiologia social Antinomies and epistemological "sutures" between the social-biological and the collective-individual within the field of social epidemiology - Djalma A. de Melo-Filho (Universidade de São Paulo, 1996)
A complexidade do objeto epidemiológico tem suscitado, ao longo do tempo, discussão sobre alguns elementos que o compõem, assumindo, muitas vezes, a forma de antinomias. Utilizando-se como substrato textos fundamentais, analisaram-se, no âmbito da epidemiologia social, a formulação e a proposta de solução para as antinomias biológico-social e individual-coletivo. Criticou-se a validade teórica das saídas apontadas pelo discurso epidemiológico-social para resolver o "conflito de leis" que permeia o referido objeto. Destacou-se o conceito marxista-helleriano de indivíduo para contribuir com a "sutura" dos três planos da realidade: o universal, o particular e o singular. The complexity of the epidemiological object has provoked discussion of the elements that have constituted it over time sometimes assuming the form of antinomies. By using as substract fundamental texts, the formulation and the proposal for a solution of the antinomies between the social-biological and the collective-individual are been analysed. The validity of the theoretical wasy ahead indicated by the epidemiological discourse for the solution of the conflict of "laws" that surround this object are been criticized. The concept of the individual in Marx and Heller is been used to contribute to the "suturing" of the three strata of reality: the universal, the particular and the singular.